Coral reefs restoration initiatives in Costa Rica: ten years building hope - Alvarado, Juan José (2025)
Introduction: Costa Rica has been recognized worldwide for its high biodiversity and the conservation actions it has implemented. One of the most iconic ecosystems are coral reefs, which have experienced strong anthropogenic and natural pressures in recent years. To ensure these ecosystems’ preservation and services, a series of coral restoration initiatives have emerged in the last ten years along both Pacific and Caribbean coasts. Objective: To document the different advances of the various coral restoration initiatives Costa Rica’s Pacific and Caribbean coasts. Methods: This review focuses on the implementation of the different reef restoration efforts, indicating the restoration techniques used, the coral species used in the nurseries, as well as the general results of survival and growth. Results: The first coral restoration project in Costa Rica occurred in the 1990s and was the only such effort until the 2010s. In 2013, a pilot project began in the Golfo Dulce area, which was later replicated in other areas of the country, such as Manuel Antonio, Sámara, and Bahía Culebra on the Pacific coast, and more recently in Punta Cahuita in the Caribbean. Various artificial structures have been used as nurseries in the water column such as trees and ropes, and benthic structures such like A-frames, tables, and spiders, the former being very effective for branching species (Pocillopora spp.), while the rest have worked successfully both for branched and massive species (Pavona spp. and Porites spp.). The results shows a growth rates have been between 6 and 9 cm/year, with survival of 60–90 % of the branching and massive colonies. All sites were seriously affected by the El Niño 2023 phenomenon, with high bleaching values ​​and loss of colonies in the nurseries and on the reef. Conclusion: Despite geographic and oceanographic distinctions, these projects have emphasized local engagement and perception of coral reefs, fostered intersectoral public-private collaborations for financial and human resources, and operated within established governmental regulatory frameworks. All projects face vulnerabilities such as El Niño events and Harmful Algal Blooms.